2007
DOI: 10.1016/j.matbio.2006.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of differentiating embryonic stem cells expressing dominant negative fibroblast growth factor receptor 2

Abstract: Embryonic stem (ES) cells are derived from the inner cell mass of the blastocyst and can be cultured as three-dimensional embryoid bodies (EBs) in which embryonic pregastrulation stages are faithfully mimicked. Fibroblast growth factor receptors (mainly FGFR2) are involved in the first differentiation events during early mammalian embryogenesis. It has been demonstrated that the presence of FGFR2 is a prerequisite for laminin-111 and collagen type IV synthesis and subsequently basement membrane formation in EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Our results also showed that FGFR2 is the key signaling receptor for exogenous FGF‐2 in hESCs, even though its expression is much lower than another FGF‐2‐cognate receptor, FGFR1. This is consistent with the role of FGFR2 during mammalian development, where FGFR2 regulates the outgrowth and maintenance of the ICM, basement membrane formation, and epithelial differentiation [41–44]. Simultaneously, this raises the issue of what the role of dominantly expressed FGFR1 is in hESCs.…”
Section: Discussionsupporting
confidence: 76%
“…Our results also showed that FGFR2 is the key signaling receptor for exogenous FGF‐2 in hESCs, even though its expression is much lower than another FGF‐2‐cognate receptor, FGFR1. This is consistent with the role of FGFR2 during mammalian development, where FGFR2 regulates the outgrowth and maintenance of the ICM, basement membrane formation, and epithelial differentiation [41–44]. Simultaneously, this raises the issue of what the role of dominantly expressed FGFR1 is in hESCs.…”
Section: Discussionsupporting
confidence: 76%
“…From our microarray studies, we primarily expected that the expression of genes involved in the conversion of stem cells to a polarized epithelium would be altered. Examples of such genes are Nanog and Zfp42 (Rex-1), which have been shown to be expressed at a higher level in EBs with defective fibroblast growth factor receptor signalling but which are normally suppressed during early developmental events (Meszaros et al 2007). However, we have noted no differences in the expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we conducted an extensive microarray-based gene expression analysis of dnFgfr2-transfected EBs and presented a catalogue of genes whose expression was significantly influenced by deficient Fgfr signalling. Among the strongly downregulated targets, a number of not yet annotated genes were identified, including the hitherto uncharacterized gene 1110032E23Rik (Meszaros et al, 2007). As confirmed by RTInt.…”
Section: Abstract: Ened Embryonic Development Epithelium Fgf/fgfrmentioning
confidence: 80%
“…PCR analysis, the expression level of this gene was reduced in dnFgfr2 EBs, indicating that this novel gene might be a target of the Fgfr signalling pathway (Meszaros et al, 2007). In the current study, we investigated the gene expression of 1110032E23Rik during mouse and Xenopus laevis embryonic development.…”
mentioning
confidence: 92%